Skin Ageing: A Progressive, Multi-Factorial Condition Demanding an Integrated, Multilayer-Targeted Remedy - Liang Y; Su W; Wang F (Dove Medical Press, 2023)
Yihuai Liang,1,2 Wenrou Su,1,2 Feifei Wang1- 3 1Research and Development Center, Yunnan Botanee Bio-Technology Group Co. Ltd, Shanghai, People's Republic of China; 2Yunnan Yunke Characteristic Plant Extraction Laboratory Co. Ltd, Kunming, Yunnan, People's Republic of China; 3Medaesthee (Shanghai) Biotechnology Co., Ltd, Shanghai, People's Republic of ChinaCorrespondence: Feifei Wang, Research and Development Center, Yunnan Botanee Bio-Technology Group Co. Ltd, No. 999 Huaxu Road, Shanghai, 201702, People's Republic of China, Tel +86 21 39880807, Email wangfeifei@winona.cnAbstract: Of the human organs, skin is the most visible one that displays the manifestations of ageing. It has a very intricate microanatomical structure and performs several key physiological functions. The pathophysiology of cutaneous ageing is characterized by deterioration of structural stability and functional integrity, implying a continuous reduction in maximal function and reserve capacity, as a result of the accumulating damage due to both intrinsic and extrinsic factors. Elimination of unfavorable expressions associated with facial and cutaneous ageing is the key patient demand in aesthetic dermatology. Even though the progress has been made in nonsurgical therapies like fillers and lasers, non-invasive interventions by using skin care products designed for rejuvenation at an early stage are the most popular and accessible solution among people. In this review, we have scrutinized the ageing-associated cutaneous changes at molecular, cellular and tissue levels. To optimize the ageing process towards a healthy skin, we propose an integrated, multilayer-targeted intervention, which involves both topical application of anti-ageing formulations from outside and oral supplementation from inside. Additionally, several promising naturally derived ingredients are reviewed from an anti-aging perspective. Most of them possess various bioactivities and may contribute to the development of the mentioned anti-ageing remedy.Keywords: skin barrier, skin ageing, causative factors, anti-ageing remedy, naturally derived ingredients